Teguh dalam Iman: Kepemimpinan Yosua dalam Menaklukkan Tanah Perjanjian - Grecetinovitria Merliana Butar-butar; Fritcen Vanny M Pardede; Yusi Cinta Siagian (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Leadership of Joshua in the Bible, highlighting his role, method, results of discussion, and relevance in modern context. Joshua was chosen by God as the successor of Moses, leading the Israelites towards the land of Canaan with courage, steadfastness, and obedience to God's commands. The research method employed was a qualitative approach using literature review, exploring the leadership values of Joshua in the context of the Bible. Joshua's selection by God, preparation and strategies in conquering the Promised Land, and his obedience to God's commands were discussed. There are leadership principles embodied by Joshua, such as firmness, courage, good character, innovation, steadfastness, and moral principles, which are relevant for modern leaders in creating stable and innovative environments. These principles encourage integrity, courage, and the ability to overcome challenges with appropriate solutions, while maintaining focus on the main goals and building strong relationships with the team.